The Problem of the Subject and Object of Cognition in Postnonclassical Science - Oganyan, Kadzhik; Ogorodnikov, Vladimir; Oganyan, Karina; Prozorovskaya, Kamilla; Bashkirtsev, Victor; Solovyov, Anatoly (Տիգրան Մեծ)
The article clarifies the change in the content and essence of subject-object relations in different periods of the development of scientific knowledge. The analysis of the main interpretations of the concept of “subject” in post-non-classical science is carried out. Attention is drawn to the negative consequences for scientific cognition of attempts on the one hand to break the irreducible unity of subject-object relations, and on the other -to bring this unity to a complete fusion of components. The authors, based on the evolutionary connection between the formation of human consciousness and cognition in the process of activity, reveal the main de-terminants of the evolution of subject-object relations.
Keywords: Methodology; Philosophy